Survival analysis of patients seen at the Ottawa Hospital Regional Cancer Centre with early breast cancer, 1985--2001: Effect of changes in stage and adjuvant chemotherapy over time - Nicholas, Garth (University of Ottawa (Canada), 2007)
Breast cancer is the commonest cancer affecting Canadian women. Recent decades have seen a trend of decreasing breast cancer mortality. This has been attributed to several causes, including greater use of screening mammography and increased efficacy of adjuvant chemotherapy. We studied the effect of these two factors on the overall survival of breast cancer patients at the Ottawa Hospital Regional Cancer Centre. Data were collected from 2985 charts from the years 1985, 1988, 1992, 1995, 1998, and 2001. Adjuvant chemotherapy was associated with a decreased hazard of death from any cause (HR=0.783 p=0.0208). A decrease in mean tumour size seen over the time period of the study is potentially attributable to mammography screening. Decreased tumour size was associated with a decreased hazard for death (HR 0.986 p<0.0001). No difference in overall survival between earlier and later cohorts could be demonstrated, perhaps due to shorter follow up in later cohorts.
Keywords: Health Sciences, Epidemiology.; Health Sciences, Health Care Management.; Health Sciences, Oncology.